A Randomized Pilot Study Comparing the Impact of Strengthening-Based Running Training with Only Running on the Incidence of Running-Related Injuries among Novice Runners - Anh Phong Nguyen; Noé Abeels; Romain Van Brussel; Benoit Pairot de Fontenay (MDPI AG, 2024)
Background: Running-related injuries (RRI) are common in novice runners. Reducing early training running volume with strengthening activities may improve RRI without impeding running performance. Objectives: 1. Gather feasibility data for a randomized, controlled trial comparing a strengthening-based program to a conventional running program; 2. Assess RRI; and 3. Assess running performance. Methods: Seventy-four university students (38 females, 21 ± 2.3 years, 68.2 ± 10.8 kg, BMI: 22.6 ± 2.97), all novice runners, were randomized in two groups, i.e., a strengthening and running group (INT) and a running group (CON). The completed sessions, RRI, dropout, and maximal aerobic speed were recorded through an online application. Results: The INT group had 52.6% attrition, while the CON group had 41.7%. The INT group had 56.6% adherence, while the CON group had 45.7%. The Chi-square test showed no significant difference in RRI incidence across groups (CHI2 = 2.958, p value = 0.08). A two-way ANOVA showed no significant difference in maximal aerobic speed across groups (p = 0.822) or before and after training (p = 0.304). Conclusions: This pilot study confirmed the feasibility of this randomized, controlled trial with a needed sample size of 194. However, novice runners had greater attrition rates when starting. Based on those limited data, strengthening activities that replaced running volume did not improve RRI or maximal aerobic speed.